Development of organizational healing scale: validity and reliability study - Karsantık, İsmail; Çayak, Semih (Frontiers in Psychology, 2025)
IntroductionAdverse and destructive situations can have a significant and long-lasting impact on organizational members, resulting in considerable disruption to organizational functioning. The occurrence of negative or traumatic events in organizations can be attributed to a range of factors, including natural adversities, as well as intentional or human-induced crises. The concept of organizational healing encompasses both the processes that enable an organization to regain functionality following adversity and the strategies that facilitate enhanced performance in the period following trauma or harm. Recent advances have highlighted the topic of organizational healing, particularly in relation to how organizations can recover from significant traumatic events and return to their pre-disaster state. This study aimed to develop the Organizational Healing Scale by verifying its reliability and validity.MethodsThe item pool for the organizational healing scale was developed with the objective of ensuring its applicability for researchers and participants by adhering to the principles of scientific rigor and practicality. In this context, an item pool of 32 items was created. To ensure construct validity, EFA and CFA were conducted, and for content and face validity, expert opinion was consulted. Validity was also ensured through convergent and discriminant validity. Reliability was tested using Cronbach's alpha coefficient value.ResultsThe two components (individual priority, organizational priority) identified through EFA as contributing to the construct validity of the scale were subsequently confirmed by CFA. The fit indices for the scale were at satisfactory level. The Cronbach Alpha coefficient value demonstrated that both components were reliable.DiscussionA review of the results indicated that the organizational healing scale is a valid and reliable instrument for measuring the healing levels of organizations with respect to the component under consideration.